The Hungarian patient : social opposition to an illiberal democracy - Van Til, Jon; Krasztev, Peter (Central European University Press, 2015)
This book presents compelling essays by leading Hungarian and foreign authors on the variety of social movements and parties that seek influence and power in a Hungary mired in deep and manifold crisis. The main question the volume tries to answer is: what can we expect after the fall of the semi-authoritarian Orbán regime in Hungary. Who will be the new players? What are their backgrounds? What are their political and social ideals, intentions and methods? The studies in the first section of the volume provide the reader with the reasons of the emergence of these new movements: a deep analysis of the historical, political and cultural background of the current situation. The second part contains essays and case studies which challenge the movements and parties involved to look beyond their current ineffectiveness, and to find ways of meeting the challenges that would allow them to exercise responsible and effective leadership in their time and place.